Disability, Poverty, and Material Hardship since the Passage of the ADA - Drew, Julia A. Rivera (Disability Studies Quarterly, 2015)
The past 25 years have seen an unprecedented expansion in formal civil rights for people with disabilities that, among other things, was predicted to improve their economic well-being. Studies of economic well-being among people with disabilities have traditionally focused on employment and earnings, despite the fact that a minority of people with disabilities are employed. More recent literature has expanded to include measures of income poverty and material hardship, but has not examined trends in these dimensions of economic well-being over time or across different groups of people with disabilities. The current study uses nationally representative data covering the 1993-2010 period to examine trends over time in cross-sectional and dynamic measures of income poverty, and multiple dimensions of material hardship. It also describes differences in time trends by education, sex, race/ethnicity, and employment status among people with disabilities in income poverty and any material hardship. Levels of both material hardship and income poverty are high across the entire period for all groups, but while material hardship remains at the same level between 1993 and 2010, income poverty declines. These findings show that there has been little improvement over the past two decades in the economic well-being of people with disabilities, and additional research is needed to understand the mechanisms that keep even groups that are relatively privileged — college graduates and full-time, full-year workers — at very low levels of economic well-being.